Strategies to Improve Arabic Speaking Skills for Islamic Boarding School Students - Ahmad Mubaligh; Risna Rianti Sari; Elma Diana Novitasari (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This study aimed to describe information about the strategies used to improve Arabic speaking skills for students at Islamic boarding school al-Ishlah Lamongan. This research used descriptive-qualitative research, with the type of case study, with male students as research subjects. Data collection techniques used were observation, interviews, and documentation. The results of this study were the strategies used to improve Arabic speaking skills for al-Ishlah Islamic boarding school students are: the use of direct methods in the teaching process in diniyah school and teaching in formal institutions (Madrasah Aliyah) on Arabic language materials and Islamic materials, giving vocabularies and conversation practices carried out every day after Isha' prayers and shubuh prayers, practicing Arabic speech once a week, and creating an Arabic language environment to provide opportunities for students to practice speaking Arabic and communicating with Arabic.